2017
DOI: 10.1021/acs.chemmater.7b00671
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cu2ZnSnS4 during Non-Equilibrium Annealing with Quasi-in Situ Monitoring of Sulfur Partial Pressure

Abstract: Chalcogen based materials like Cu2ZnSnS4 (CZTS) have drawn extensive attention for applications such as photovoltaics and water splitting. However, inability to monitor the sulfur partial pressure (PS2) during non-equilibrium annealing process at high temperature complicates the synthesis of CZTS with controlled optoelectronic properties. Here we demonstrated that PS2 can be monitored by investigating the Sn-S phase transformation. We showed that PS2 drops considerably over the annealing time, causing gradual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 45 publications
6
42
1
Order By: Relevance
“…Analysis of the X‐ray diffraction (XRD) spectra, see Figure a, showed that the films reacted with S and formed preferentially SnS 2 at lower temperatures and Sn 2 S 3 at higher temperatures. This observation is consistent with previous findings related to the behavior of Sn and S content in the present anneal setup . It follows from the fact that the partial pressure of S ( P s ) in the initial phase of the anneal increases rapidly initially as the elemental S evaporates and then decays during the rest of the anneal time as the system (graphite box) is not fully tight (see, e.g., a previous study).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Analysis of the X‐ray diffraction (XRD) spectra, see Figure a, showed that the films reacted with S and formed preferentially SnS 2 at lower temperatures and Sn 2 S 3 at higher temperatures. This observation is consistent with previous findings related to the behavior of Sn and S content in the present anneal setup . It follows from the fact that the partial pressure of S ( P s ) in the initial phase of the anneal increases rapidly initially as the elemental S evaporates and then decays during the rest of the anneal time as the system (graphite box) is not fully tight (see, e.g., a previous study).…”
Section: Resultssupporting
confidence: 93%
“…For the devices with Mo back contacts in this study, long anneal times (at 580 °C) typically result in deteriorated devices due to loss of S and Sn according to literature . In this study, however, it was repeatedly found that long anneal times resulted in not only working devices, but also better devices compared with those processed with shorter anneal times.…”
Section: Resultssupporting
confidence: 49%
“…33−36 The poor capability of the annealing reactors to maintain high S and Se partial pressure with time due to leakage or vapor absorption in the reactor walls has also been associated with Sn loss. 37 The evaporation of SnSe 2 occurs incongruently as represented by eqs 1 and 2. 38 Under high Se partial pressure, SnSe 2 would be stabilized as eq 1 would proceed toward the lefthand side.…”
Section: Methodsmentioning
confidence: 99%
“…3 It has been shown that both etching with (NH 4 ) 2 S solution and using thermal evaporation during the annealing process are effective approaches for removing SnS on CZTS surface. 8 Regarding the CZTS rear, SnS could form due to the initial CZTS composition 23 as well as the back contact decomposition. 24 Therefore, to control the SnS formation on the CZTS rear, efforts to develop suitable CZTS composition and to passivate the back contact are required.…”
mentioning
confidence: 99%